The relationship between neck muscle strength and duration of computer work among women employees / Siti Rusyida Rohim - Siti Rusyida , Rohim (2017)
The usage of computers is common among workforce around the globe. The employees are necessitated to use the computer intensively to help the organizations to increase work quality, and efficiency to go through rapid development era. However, prolonged use of computer is often associated to neck disorder, which could reduce work productivity and may bring a socio-economic impact. Hence, an exploratory study is required to investigate the risk factors and problems of neck pain among computer workers. This study has three specific objectives. The first objective was to identify the individual, physical and psychosocial influence to neck pain among women in office environment. The second objective was to determine the relationship between the duration on computer task with the neck muscle strength and perceived neck pain. The last objective was to build a generic pattern of changes in neck muscle strength and perceived neck pain with time spent on computer task. Fifty-one women employees who used computer to perform main task have completed a set of questionnaire to obtain demographic, workstation design and task demand information. Sixteen selected participants were involved in the second phase of data collection. In this phase, neck muscle strength measurement and perceived neck pain rating were taken periodically throughout the computer work experiment in order to observe the pattern of changes in neck muscle strength and perceived neck pain over time. The results from questionnaire reported the significant risk factors associated with higher neck pain severity were not using vision correction, using a few fingers during typing, using none adjustable backrest chair, using telephone and keyboard concurrently for at least 8 times/day and sitting at workstation for at least 2 hours before taking a break. This result suggests that using keyboard in improper manner may lead to neck pain and higher severity. The results taken from measurements during the experiment showed that neck muscle strength in extension and flexion decreased significantly after 40 minutes of typing, while the perceived neck pain rating increased significantly after 20 minutes of typing. Overall, these results suggest that the workers may perceive significant neck pain even with slight reduction of neck muscle strength. In general, these findings may give an insight to the organization to take action in proper job scheduling especially in computer working duration to reduce the incidence of unwanted injuries. Keywords: Neck muscle strength, Neck pain, Computer User, Musculoskeletal disorder, Female employee.